Extracellularly Extruded Syntaxin‐4 Binds to Laminin and Syndecan‐1 to Regulate Mammary Epithelial Morphogenesis. Issue 4 (16th August 2016) - Shirai, Kota; Hagiwara, Natsumi; Horigome, Tomoatsu; Hirose, Yuina; Kadono, Nanako; Hirai, Yohei
ABSTRACT: Epithelial morphogenesis in the mammary gland proceeds as a consequence of complex cell behaviors including apoptotic cell death and epithelial‐mesenchymal transition (EMT); the extracellular matrix (ECM) protein laminin is crucially involved. Syntaxins mediate intracellular vesicular fusion, yet certain plasmalemmal members have been shown to possess latent extracellular functions. In this study, the extracellular subpopulation of syntaxin‐4, extruded in response to the induction of differentiation or apoptosis in mammary epithelial cells, was detected. Using a tetracycline‐repressive transcriptional system and clonal mammary epithelial cells, SCp2, we found that the expression of cell surface syntaxin‐4 elicits EMT‐like cell behaviors. Intriguingly, these cells did not up‐regulate key transcription factors associated with the canonical EMT such as snail, slug, or twist, and repressed translation of E‐cadherin. Concurrently, the cells completely evaded the cellular aggregation/rounding triggered by a potent EMT blocker laminin‐111. We found that the recombinant form of syntaxin‐4 not only bound to laminin but also latched onto the glycosaminoglycan (GAG) side chains of syndecan‐1, a laminin receptor that mediates epithelial morphogenesis. Thus, temporal extracellular extrusion of syntaxin‐4 emerged as a novel regulatory element for laminin‐induced mammary epithelial cell behaviors. J. Cell. Biochem. 118: 686–698, 2017. © 2016 Wiley Periodicals, Inc. Abstract : In response to differentiation/apoptosis signals, subpopulation of mammary epithelial cells extrudes syntaxin‐4 extracellularly. Extracellular syntaxin‐4 binds to laminin and its receptor syndecan‐1, leading to deregulate laminin signals for epithelial morphogenesis.